2004
DOI: 10.1142/s0218271804005912
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Accretion Shocks in Viscous Flows With Cooling Effects

Abstract: Low angular momentum accretion flows can have standing and oscillating shock waves. We study the region of the parameter space in which multiple sonic points occur in viscous flows in presence of various cooling effects such as bremsstrahlung and Comptonization. We also quantify the parameter space in which shocks are steady or oscillating. We find that cooling induces effects opposite to heating by viscosity even in modifying the topology of the solutions, though one can never be exactly balanced by the other… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Furthermore, many authors have pointed out that shocks may undergo radial, vertical or non‐axisymmetrical oscillations (Molteni, Toth & Kuznetsov 1999; Gu & Foglizzo 2003), although they are generally never ruined by these oscillations. In Das & Chakrabarti (2004), bremsstrahlung cooling was also added, bearing in mind that it is a very inefficient cooling process (Chattopadhyay & Chakrabarti 2000), and a complete set of global solutions of viscous transonic flow with and without shocks was presented. The hot and dense post‐shock flow, which basically acts as a ‘boundary layer’ for the black holes, could be the natural site of hot radiation in accretion discs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many authors have pointed out that shocks may undergo radial, vertical or non‐axisymmetrical oscillations (Molteni, Toth & Kuznetsov 1999; Gu & Foglizzo 2003), although they are generally never ruined by these oscillations. In Das & Chakrabarti (2004), bremsstrahlung cooling was also added, bearing in mind that it is a very inefficient cooling process (Chattopadhyay & Chakrabarti 2000), and a complete set of global solutions of viscous transonic flow with and without shocks was presented. The hot and dense post‐shock flow, which basically acts as a ‘boundary layer’ for the black holes, could be the natural site of hot radiation in accretion discs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown by Chakrabarti (1989) that low angular momentum, non‐dissipative flows produce axisymmetric standing shock waves in tens of Schwarzschild radii, but the presence of a large viscosity (Chakrabarti 1990, hereafter C90) will remove the shock wave since the Rankine–Hugoniot relation is not satisfied in a highly dissipative flow. A confirmation of such an assertion, originally made in the context of the isothermal flows, came both through numerical simulations (Chakrabarti & Molteni 1995, hereafter CM95) and theoretical studies of flows with a more general equation of states (Chakrabarti 1996a, hereafter C96; Chakrabarti & Das 2004; Das & Chakrabarti 2004). The theoretical works showed that the topology of the flow is modified when viscosity is added, and beyond a critical viscosity, the centrifugal pressure supported shocks do not form.…”
Section: Introductionmentioning
confidence: 85%
“…2,15 It would be interesting to study how the dissipative processes modify the shape of the duct. Particularly important is the fact that above a critical viscosity the standing shock itself disappears.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%